신호처리 및 추적 알고리즘을 고려한 항공기탑재 레이다 거리 분해 성능 검증 - 박연희; 김용민; Yeonhee Pak; Yong-min Kim (한국항행학회논문지, 2023)
Range resolution is the ability to distinguish different targets placed in same angular direction but at different distances from the radar. Normally, Range resolution requirement is defined as the width of transmitting pulse. The width of transmitting pulse does not mean the ability to distinguish two different targets. Range resolution performance to detect and track targets separately depends on the signal processing and tracking algorithm not only the width of transmitting pulse. This paper analyzes the processing steps in algorithms to affect the range resolution performance and verifies the results by roof-lab ground test using beacon signal. As a result, to track targets with the same angular position separately, it is desirable to have larger range difference than plot-track association test gate. 레이다의 주요 성능 규격 중 하나인 거리 분해능은 동일한 속도 및 각도의 두 표적을 거리 상으로 분해할 수 있는 성능과 관련된 지표이다. 일반적으로 레이다 성능 규격에 정의된 분해능은 실제 두 표적 분해 관점이 아닌 송신 펄스 폭으로 정의된다. 송신 펄스 폭 수치는 설계 측면의 성능 규격일 뿐, 두 표적을 분해할 수 있는 최소 거리를 의미하는 것이 아니다. 본 논문에서는 송신 펄스폭과 레이다 알고리즘을 동시에 고려하여 동일한 속도 및 각도 정보를 가지는 두 신호가 거리 차이로 분해되어 개별 추적개시로 이어질 수 있는 최소 거리차이에 대해 분석한다. 분해능 이외의 다른 외부 간섭을 배제하기 위해 비콘(Beacon) 신호를 활용한 루프랩 (Roof-lab) 환경에서 지상시험을 수행하였고, 탐지 단계에서는 신호처리 알고리즘에 의해 개별 탐지 성능이 결정되고, 추적 형성 단계에서는 데이터 연관을 통한 중복성 검사 알고리즘에 의해 분해 성능이 결정되는 것을 확인하였다.